(3TQM Ydi TQM GdefXheI aj GdMceIs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3hGdeJCNQ dCf GdeJCNQ eJUaG Hg eLGRG adG jchf edGc ddJbOe hGdJCNQ, bhdg(B: (3HgPG GdfMh, Cj HfMh (B... (3hEdG HfMh GdJbjO HGdMbjbI Ch GdeLGR jchf eNJUGs
(3BNQgG (B:s
(3BNQgG(B: (3hEfeG jUM MedgG dCLd GJMGOgeG aj GdhLhO NGQLG adh cGfJ Gdgjhdi hGdUhQI ZjQ eJMOjf NGQLG deG UM GdMed dCfg de jcf aj GdLfS hGdaYd eJNPjf NGQLGs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs